Análise da aplicação de métodos europeus de vulnerabilidade intrínseca ao carste tropical da região da APA Carste de Lagoa Santa - Thaís Guedes Ayres Silva (2022)
The Intrinsic Vulnerability Analysis in the Environmental Protection Area Karst region of Lagoa Santa was carried out in this work through two parametric systems, developed with specific application for the karstic environment. However, the methods were developed in Europe to be applied in temperate and Mediterranean regions, opposed to the application area of this study, which is characterized as a humid tropical climate karst. Therefore, the EPIK and SINTACS methods were applied to the area in its original form and underwent modifications to adapt to the diverging features between the regions of development and the site in question. Hence, this dissertation is based on the presentation of these results, mapping the area in categories of vulnerability to the contamination of the current aquifers in the region, in addition to an analysis of the application of these European methods in a tropical region, highlighting the differences applied to adapt the methods and comparing them to list the positive and negative factors of each parameter and, finally, the application of weights to each attribute for the region of study. The modification in the EPIK method was due to a new parameterization of the soil thickness indices, comparing their maximum value obtained in a temperate climate area in Switzerland, where the method was developed, to the maximum value measured in a humid tropical climate, at the study site in Brazil, as well as the alteration of the assigned weights to each parameter, bringing a greater importance to the factors of protection layer and karst development. In the SINTACS method, the change was made in the new weight assignment, increasing the importance given to the sort of soil cover factor and reducing the weight of recharge and topographic slope, since this method does not consider the protective cover of vegetation. In short, the chosen methodologies are suitable for application in the karst environment, presenting attributes and weighting up different parameters for the analysis of this sort of environment. The EPIK method, exclusively developed for the karst environment, raises specific factors to the analysis of karst features, such as rock masses, sinkholes and also the development of karst conduits, making the method a model for application in this environment. The SINTACS method, which was not developed exclusively for the karst environment, does not bring forward these specific parameters, but applies a weighting order of the attributes that is reliable to the most important factors of this environment, and also easy to apply. The achieved results shows that the SINTACS method is more protective, attributing a greater vulnerability to a large part of the area.